2009
DOI: 10.21608/jappmu.2009.119378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromium Picolonate on Growth, Blood Parameters and Carcass Traits of Growing New Zealand White Rabbits.

Abstract: Total of 20 New Zealand White (NZW) male bunnies weaned at 5 weeks of age having average live body weight of 620±20.2 g were used in experiment study to study the effect of daily treatment of chromium picolinate (CrP) on growth performance in relation to blood parameters, carcass traits, chemical analysis of meat and economic efficiency. Rabbits were divided into 2 groups, 10 animals in each. Rabbits in the 1 st group were served as control (G1) without any treatment. However, those in the 2 nd group (G2) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
2
2
1
Order By: Relevance
“…These results are logic and in accordance with level of Cr treatment in different treatment groups. In this respect, El-Ayek et al (2009) found similar values of control group fed similar diet to that fed in this study. Also they observed similar trend of increasing Cr concentration in serum of Cr treated than in control rabbits by about 15%.…”
Section: Blood Parameterssupporting
confidence: 86%
See 4 more Smart Citations
“…These results are logic and in accordance with level of Cr treatment in different treatment groups. In this respect, El-Ayek et al (2009) found similar values of control group fed similar diet to that fed in this study. Also they observed similar trend of increasing Cr concentration in serum of Cr treated than in control rabbits by about 15%.…”
Section: Blood Parameterssupporting
confidence: 86%
“…Such results indicated nearly similarity in growth performance of bunnies produced from rabbit does in all treated does and those in the control group, but the superiority of does in INS and Cr+INS groups was mainly related to viability rate of bunnies throughout the suckling period. Similar reduction in growth rate of NZW and California bunnies produced by does treated with Cr at two levels as compared to the controls was reported by El-Ayek et al (2009) and Nasif ( 2008), respectively. Table (7 In accordance with the present results, Lindemann et al (2004) found that supplemental CrP increased the number of pigs born live per litter, but decreased individual birth weight of total pigs born, being 1.61, 1.57, 1.47, and 1.56 kg for levels of 0, 200, 600, 1000 ppb as-fed basis, respectively.…”
Section: Growth Performance Of Bunniessupporting
confidence: 84%
See 3 more Smart Citations